Annual Bluegrass Control on Putting Greens from Three or Four Years of Season‐long Applications of Herbicides or Plant Growth Regulators in Three States. Issue 1 (26th June 2015) - Reicher, Zachary; Sousek, Matt; Patton, Aaron; Weisenberger, Dan; Hathaway, Aaron; Calhoun, Ronald
Abstract : Annual bluegrass ( Poa annua L.) may be the most troublesome and studied weed on golf courses in the United States. Given the genetic variability of annual bluegrass and its ability to adapt to different environments, it is important to understand how control methods vary across environments or regions. Our objective was to evaluate seven season‐long regimes of herbicide or growth regulators for annual bluegrass control in creeping bentgrass ( Agrostis stolonifera Huds.) putting greens over 3 or 4 years in three states in the midwestern United States. Depending on the product, applications were made as often as every 2 weeks from April through September. Effectiveness of treatments varied widely by location and time, with treatments most effective in Indiana and Nebraska. Paclobutrazol was the most effective plant growth regulator for annual bluegrass control, followed closely by flurprimidol. Intermediate at reducing annual bluegrass was flurprimidol + trinexapac‐ethyl and trinexapac‐ethyl was ineffective. Among herbicides, the now discontinued experimental cumyluron was most effective and four applications of bispyribac‐sodium at 2 oz/acre every 2 weeks in August and September was more effective than 1 oz/acre applied every 2 weeks from May through September or applications of cumyluron. Though a number of products will reduce annual bluegrass on golf greens, overall control was relatively low, reinforcing the need to maximize cultural practices before attempting chemical control. Furthermore, our results reinforce the importance of superintendents' experimenting and refining treatment regimes in their specific location to maximize efficacy.